2023
DOI: 10.3390/foods12071474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heating Treatment on Functional and Structural Properties of Liquid Whole Egg

Abstract: Liquid whole egg (LWE) products have many advantages such as convenient transportation, easy production and are safe. However, LWE has a short shelf life and high thermal sensitivity, so suitable heating treatment is the key to the production of LWE products. The aim of this study is to investigate the effects of heating treatments conditions (at 55–67 °C for 0–10 min) on the emulsification, foaming activity and rheological properties of LWE. The results indicated that the emulsifying activity of LWE had no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For these reasons, it is believed that the pasteurized liquid egg whites in this study showed no significant quality deterioration under the evaluated temperature and time conditions. On the other hand, the study (Wang et al, 2023) Considering these reasons and our results, we believe that the functional properties of the pasteurized liquid egg white and yolk in this study have not experienced relevant changes. Moreover, since it is well known that location (Yamamoto et al, 2019) and type (Russell et al, 2019) of impellers can affect the flowing behavior during agitation process, it is desired in further studies to cover the effect of these variables on the functional quality properties changes of liquid eggs using the 3D model developed in this study and the kinetics of reaction of each property changes.…”
Section: Tpd Degree Evaluationmentioning
confidence: 63%
See 3 more Smart Citations
“…For these reasons, it is believed that the pasteurized liquid egg whites in this study showed no significant quality deterioration under the evaluated temperature and time conditions. On the other hand, the study (Wang et al, 2023) Considering these reasons and our results, we believe that the functional properties of the pasteurized liquid egg white and yolk in this study have not experienced relevant changes. Moreover, since it is well known that location (Yamamoto et al, 2019) and type (Russell et al, 2019) of impellers can affect the flowing behavior during agitation process, it is desired in further studies to cover the effect of these variables on the functional quality properties changes of liquid eggs using the 3D model developed in this study and the kinetics of reaction of each property changes.…”
Section: Tpd Degree Evaluationmentioning
confidence: 63%
“…For these reasons, it is believed that the pasteurized liquid egg whites in this study showed no significant quality deterioration under the evaluated temperature and time conditions. On the other hand, the study (Wang et al, 2023) also reported changes in the emulsifying properties of LWE during water bath treatment. The emulsifying activity and emulsifying stability demonstrated increases in the temperature range of 55–64°C within 2 min and 8 min treatment, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, higher temperatures may lead to increased protein denaturation, and decreased protein solubility that reduces the foaming activity. 83 Hence controlling the temperature-sensitive proteins from denaturation is challenging in conventional heating methods.…”
Section: Different Techniques and Additives Influencing Egg Foaming B...mentioning
confidence: 99%